Implementing a Dictionary Culture in South Africa: An Attempt at a General Framework for the African Languages - Klein, Juliane (Lexikos, 2007)
Abstract: The development of a dictionary culture consists of three main phases: (a) the information phase, (b) the learning phase and (c) the consolidation phase. The first step towards a new dictionary culture is to inform mother-tongue speakers of available dictionaries and their benefits for individual speakers. This information should mainly be distributed through dictionary awareness campaigns conducted in the relevant African languages and by influential mother-tongue speakers. The main difficulty of the learning phase consists in the teaching of different groups, for example lexicographers, teachers and students, as well as adults who want to consult a dictionary effectively. Although a basic knowledge of lexicography is useful for teachers, a natural association with dictionaries as well as an intimate knowledge of dictionaries is more important. An intimate knowledge of dictionaries includes, among others: the different dictionary types, the contents of dictionaries and the know-how to find the sought-for word. The last phase is the consolidation phase in which the association with dictionaries will change from an uncommon to a normal activity.Keywords: DICTIONARY CULTURE, INFORMATION, NATIONAL LEXICOGRAPHIC UNITS, DICTIONARIES, AFRICAN LANGUAGES, DICTIONARY AWARENESS CAMPAIGNS, EMPOWERMENT, TEACHING PHASE, USER, MEDIA, CONSOLIDATION PHASE, INCLUSIVE MODELZusammenfassung: Implementierung einer Wörterbuchkultur in Südafrika: Ein Versuch eines allgemeinen Modells für die afrikanischen Sprachen. Die Entwicklung einer Wörterbuchkultur besteht aus drei Hauptphasen: (a) die Informationsphase, (b) die Lernphase und (c) die Festigungsphase. Der erste Schritt zu einer neuen Wörterbuchkultur ist es, Muttersprachler über erhältliche Wörterbücher und ihre Vorteile für den einzelnen Sprecher zu informieren. Diese Informationen sollen hauptsächlich durch Initiativen zum Gebrauch von Wör-terbüchern, die in den entsprechenden afrikanischen Sprachen ausgeführt werden müssen, und einflussreiche Muttersprachler verbreitet werden. Die Hauptschwierigkeit der Lernphase besteht darin, daß unterschiedlichen Gruppen zu unterrichten sind, z.B. Lexikographen, Lehrer, Schüler, sowie Erwachsene die ein Wörterbuch erfolgreich benutzen wollen. Obwohl ein grundlegendes Wissen über Lexikographie für Lehrer nützlich ist, sind der selbstverständliche Umgang mit Wör-terbüchern sowie ein Grundwissen über Wörterbücher wichtiger. Zu dem Grundwissen über Wörterbücher zählen unter anderem: Die verschieden Wörterbuchtypen, Inhalte der Wörterbücher und das Wissen das gesuchte Wort zu finden. Die letzte Phase ist die Stabilisierungsphase in wel-cher der Umgang mit Wörterbüchern von einer seltenen zu einer alltäglichen Aktivität werden soll.Stichwörter: WÖRTERBUCHKULTUR, INFORMATION, NATIONAL LEXICOGRAPHIC UNITS, WÖRTERBÜCHER, AFRIKANISCHE SPRACHEN, INITIATIVEN ZUM GEBRAUCH VON WÖRTERBÜCHERN, EMPOWERMENT, LERNPHASE, BENUTZER, MEDIEN, STABILI-SIERUNGSPHASE, INKLUSIVES MODELL